Etiology and Incidence of Bacterial Meningitis in Patients in Tobruk Medical Centre - Al-awkally, Noor Alhooda Milood; El- warred, Sara; Fakron, Abdlmanam; Ali , Mareei Al- Douakali; Ibrahim, Hamza Khalifa; Al Fraik , Nasren Gamal Saleh; Al-Awkally, Alreda Miloud; Al-awkally, Nesrine Miloud; Elbagrmi, Twfeik (African Journal of Advanced Pure and Applied Sciences, 2022)
Bacterial meningitis is a medical emergency associated with high mortality rates. Cerebrospinal fluid (CSF) culture is the gold standard for diagnosis of meningitis and it is important to establish the susceptibility of the causative microorganism to rationalize treatment. Objective of this study was to assess the seasonality of the bacterial meningitis and the antibiotic resistance of incriminated bacteria through the year in Tobruk city. This Laboratory‐based retrospective analysis of 367 CSF cultures was conducted in Tobruk Medical Centre, Tobruk, from January 2020 - December 2020. Of whom 367, 188 (59%) were male, while 179 (49%) were female. Of 367. Three isolated pathogen was Klebseilla spp 2(1%), followed by streptococcus pyogen and Staph aureus 1 (0%) equally. While 363 (99%) was no growth. The majority of cases 110 (30 %) were cultured in autumn 110 (30%) followed by winter 95 (26%) and spring 88 (24%). in our study the decreasing of bacterial isolation from CSF samples, is maybe due to several reasons such as administration of antibiotics to the patients before CSF sample culturing or the patients were infected with viral infections or the patients were not infected at all. Additional study should focus on avoidable features of vaccines, to reduce the disease problem.